The influence of Social Environment and Economic Rationality on Student Financial Literacy Literacy - Dewi, Ayu Sinta Sri; Suherti, Heti; Sartika, Sri Hardianti (Economic Education and Entrepreneurship Journal, 2023)
Financial literacy is something that needs to be examined today, financial knowledge changes not only in theory, but also in the practice of personal finance in the real world. Knowledge and finance are needed so that individuals do not get entangled in financial problems and are wise in making decisions for personal financial consistency. This study uses quantitative approach with a survey research design. Faculty of Teacher Training and Education, Siliwangi University class of 2020 participated in this study. With a simple random sampling technique of 305 students as a research sample. and questionnaires as a data collection method. The research findings show,. The social environment has a positive influence on financial literacy . Economic rationality has a positive influence on financial literacy and  Social environment and economic rationality have a positive influence on financial literacy simultaneously. The research findings show that the social environment and economic rationality have a considerable impact on financial literacy, with a coefficient of determination of 71%. If everyone does not have adequate financial literacy, the following financial problems arise: inappropriate use of credit cards, wrong choice of financial products, waste of money.Keywords: Financial Literacy, Rationality, Social EnvironmentDOI: http://dx.doi.org/10.23960/E3J/v6i2.162-167